EVALUATIONS OF SUBSTITUTES FOR AGAR IN THE BREEDING OF Diatraea saccharalis (F.) (Lepidoptera: Pyralidae - LASTRA, LUZ ADRIANA; GÓMEZ, LUIS ANTONIO (Revista Colombiana de Entomología, 1992)
Agar turns out to be the most expensive ingredient of an artificial diet used for mass rearing the sugarcane borer, Diatraea saccharalis (F.). Corncob grits and carrageenan from Brasil were tested as agar substitutes replacing 75 and 100% respectively, of the agar used regularly in a carrot-based diet. In another experiment, diets with different levels of agar replacement (50, 75, 80, 90, and 100%) were evaluated in comparison with a check diet made with the full amount of agar. Two sources of corncob material were tested as well as two different desiccation procedures. Larval survival, percentage of normal size larvae, the weight of larvae and pupae, and egg fertility were measured as response variables. No differences were detected in the development of Diatraea as a result of agar replacement by corncob grits or carrageenan, except when the former replaced agar by more than 75%; when this occurred, the number of larvae recovered decreased and the development time increased. No effect was observed when corncob from different sources or desiccated in different ways was used. Therefore, it is feasible to replace agar in the artificial diet by corncob grits or carrageenan to mass rear D. saccharalis.